Fructose, pregnancy and later life impacts. (27th October 2013) - Regnault, Timothy RH; Gentili, Sheridan; Sarr, Ousseynou; Toop, Carla R; Sloboda, Deborah M
Summary: Fructose is an increasingly common constituent of the Westernized diet due to cost and production efficiencies. Although an integral component of our pre‐industrial revolution diet, over the past two decades human and animal studies have highlighted that excessive fructose intake appears to be associated with adverse metabolic effects. Excessive intake of fructose is the combined result of increased total energy consumption and increased portion sizes of foods, which often incorporate the fructose‐containing sugars sucrose and high‐fructose corn‐syrup (HFCS). The adverse metabolic effects following excessive fructose consumption have become a hot topic in mainstream media and there is now rigorous scientific debate regarding periods of exposure, dosage levels, interactive effects with other sugars and fats and mechanisms underlying the actions of fructose. There is still a degree of controversy regarding the extent to which sugars such as sucrose and HFCS have contributed to the current epidemic of obesity and diabetes. Furthermore, an increasing number of infants are being exposed to sugar‐sweetened food and beverages before birth and during early postnatal life, highlighting the importance of determining the long‐term effects of this perinatal exposure on the developing offspring. There are limited human observational and controlled studies identifying associations of excessive sweetened food and beverage consumption with poor pregnancy outcomes. Animal research has demonstrated an increased incidence of gestational diabetes as well as altered maternal, fetal and offspring metabolic function, although the long‐term effects and the mechanism underlying these perturbations are ill defined. This review aims to understand the role of early life fructose exposure in modifying postnatal risk of disease in the offspring, focusing on fructose intake during pregnancy and in early postnatal life.